Ethanol Future Fuel for India: An Introduction - T. Vinod Kumar; S. Arunkumar; S. Ajith Arul Daniel; Vijayananth Suyamburajan; S. Padmanabhan (Techniques and Innovation in Engineering Research Vol. 3, 2022)
The increasing prosperity of India has led to a surge in the country’s vehicle population and the need for more fuel. The transportation industry must contend with a diminishing supply of fossil fuels, fluctuating crude oil costs, and more strict environmental rules. These problems may be solved by switching to other fuels. Bio-fuels are being aggressively explored because of the reduced complexity involved in their manufacture, storage, transportation, and application in internal combustion engines compared to other options. Ethanol’s higher energy density and lower environmental impact make it a promising alternative fuel. The Indian government has previously required a 10% ethanol mix in gasoline as part of a plan to cut oil imports. This study provides an introduction to ethanol as a potential replacement fuel for gasoline engines in the Indian context.